Patient Perspectives of Barriers and Facilitators of Treatment-Seeking Behaviors for Stroke Care. Issue 3 (June 2015) - Beckett, Jamie; Barley, Jessica; Ellis, Charles
Abstract : ABSTRACT: Objective: Delays in seeking treatment for stroke care are associated with greater disability and reductions in stroke outcomes. The objective of this study was to qualitatively examine facilitators and barriers to urgently seeking stroke-related care.Methods: A qualitative analytic approach was used to explore facilitators and barriers to seeking stroke care in an urgent manner. Sixty-four stroke survivors offered information related to facilitators and barriers to stroke care via a structured survey as part of a larger mixed-methods study designed to measure stroke outcomes.Results: Three themes emerged related to facilitators and barriers: (a) recognition of symptoms, (b) social support, and (c) knowledge and ability to call emergency medical services as a first response. Facilitators to urgent care-seeking behaviors included classic stroke symptoms, severe symptoms, sudden symptom onset, and high perceived level of emergency. Social support and knowledge/ability to call emergency medical services also emerged as facilitators of urgent care. Barriers to urgent care-seeking behaviors included atypical symptoms, mild symptoms, gradual symptom onset, and low perceived level of emergency.Conclusions: Individuals who experience strokes face a number of facilitators and barriers to seeking urgent care for their condition. Facilitators and barriers are associated with stroke symptoms and their personal environments. Additional study of barriers to stroke care is needed to adequately design interventions to reduce delays in seeking treatment.